Naringin Ameliorates Monocrotaline-Induced Pulmonary Arterial Hypertension Through Endothelial-To-Mesenchymal Transition Inhibition - Wu, Yonghui; Cai, Changhong; Xiang, Yijia; Zhao, Huan; Lv, Lingchun; Zeng, Chunlai (Frontiers in Pharmacology, 2021)
Pulmonary arterial hypertension (PAH) caused by enhanced arterial pressure and increase vessel resistance in the lung. Endothelial-to-mesenchymal transition (EndMT) plays key roles in the vascular remodeling in PAH. Naringin, a protective gaseous mediator in PAH, is commonly extracted from tomatoes and citrus fruits (such as grapefruits), demonstrates effects in anti-inflammation, anti-oxidants, anti-proliferation and anti-tumor effects. Meanwhile, the association of Naringin and the process of EndMT is still unclear. In this study, monocrotaline (MCT) administration (60 mg/kg) was delivered for the induction of PAH in rats. Followed by that, Naringin (concentrations: 25, 50 and 100 mg/kg/day) were used for treatments. Human Umbilical Vein Endothelial Cells (HUVECs) were stimulated with Naringin and transforming growth factor β1 (TGFβ1, 10 ng/ml). As the result, Naringin was demonstrated to inhibit EndMT and alleviate PAH progression. In particular, HUVECs, Naringin significantly suppressed the mesenchymal marker expression induced by TGFβ1 treatment, enhanced the endothelial marker expression, and inhibited the activation of ERK and NF-κB signaling pathways. To conclude, this study provided novel evidences suggesting the beneficial effects of Naringin in PAH through the inhibition of the ERK and NF-κB signaling pathways and the EndMT progression in pulmonary arteries.